2000
DOI: 10.1046/j.1525-1497.2000.01239.x
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of different management strategies for patients on chronic warfarin therapy

Abstract: OBJECTIVE:To examine the cost-effectiveness of moving from usual care to more organized management strategies for patients on chronic warfarin therapy. DESIGN:Using information available in the scientific literature, supplemented with data from a large health system and, when necessary, expert opinion, we constructed a 5-year Markov model to evaluate the health and economic outcomes associated with each of three different anticoagulation management approaches: usual care, anticoagulation clinic testing with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 45 publications
0
60
0
2
Order By: Relevance
“…Informal caregiver time costs will also be important inputs in cost-effectiveness analyses (CEAs), as recommended by The Panel on Cost-Effectiveness in Health and Medicine, 8 particularly when comparing healthcare strategies or interventions that differentially rely on informal caregivers. Few studies have explicitly assessed the impact of including time costs in CEAs, [27][28][29] and in some situations, the optimal strategy can vary depending on whether these costs are included or excluded. 27,28 For example, investigators reanalyzed the cost-effectiveness of self-monitoring of blood glucose by patients with type 2 diabetes taking oral antidiabetic medicine compared with no self-monitoring, and found that inclusion of patient time changed the cost-effectiveness ratio from $23,380 per quality-adjusted life-year (QALY) to $76,340 per QALY over a 5-year horizon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Informal caregiver time costs will also be important inputs in cost-effectiveness analyses (CEAs), as recommended by The Panel on Cost-Effectiveness in Health and Medicine, 8 particularly when comparing healthcare strategies or interventions that differentially rely on informal caregivers. Few studies have explicitly assessed the impact of including time costs in CEAs, [27][28][29] and in some situations, the optimal strategy can vary depending on whether these costs are included or excluded. 27,28 For example, investigators reanalyzed the cost-effectiveness of self-monitoring of blood glucose by patients with type 2 diabetes taking oral antidiabetic medicine compared with no self-monitoring, and found that inclusion of patient time changed the cost-effectiveness ratio from $23,380 per quality-adjusted life-year (QALY) to $76,340 per QALY over a 5-year horizon.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have explicitly assessed the impact of including time costs in CEAs, [27][28][29] and in some situations, the optimal strategy can vary depending on whether these costs are included or excluded. 27,28 For example, investigators reanalyzed the cost-effectiveness of self-monitoring of blood glucose by patients with type 2 diabetes taking oral antidiabetic medicine compared with no self-monitoring, and found that inclusion of patient time changed the cost-effectiveness ratio from $23,380 per quality-adjusted life-year (QALY) to $76,340 per QALY over a 5-year horizon. 27 To our knowledge, no studies have explicitly evaluated the impact of including and excluding caregiver time costs.…”
Section: Discussionmentioning
confidence: 99%
“…19 This is an even greater issue in routine medical care, where time in range has been documented to be even lower. 20,21 An effective low-risk therapy that could eliminate the need for OACs and their associated risks to the patient is therefore very attractive.…”
Section: Response By Holmes and Schwartz On P 1932mentioning
confidence: 99%
“…Whether patient self-testing offers overall cost savings compared to either UC or care through an AMS has been evaluated by Lafata et al [65]. Annual anticoagulation management costs per patient were estimated to be $396, $753, and $860 for UC, care through an AMS, and self-testing, respectively.…”
Section: Costsmentioning
confidence: 99%